Effect of velvet Timor deer (Rusa timorensis) supplementation to fertility status of male Wistar rats (Rattus norvegicus) - Nur Hafidzah Devi Kartika; Daud Samsudewa; Nor Basid Adiwibawa Prasetya (Universitas Sebelas Maret, 2024)
Objective: To determine the increase in calcium (Ca) and zinc (Zn) content in Timor deer blood before and after velvet powder supplementation. This study also investigates the effect of velvet powder supplementation on male rats’ fertility status.Methods: This study employed twenty males Wistar rats weighing 200 – 250 g and aged 90 days. The sample was divided into four groups: the control group (T0), the25 mg kg-1 WB-1 velvet powder (T1), the 50 mg kg-1 WB-1 velvet powder (T2) and the 100 mg kg-1 WB-1 velvet powder (T3). Ca and Zn concentrations in rat blood were determined using an atomic absorption spectrophotometer (AAS) in the Feed Nutrition Laboratory at Universitas Diponegoro. The fertility status (sperm motility, mortality and abnormality) of male rat sperm was studied. In this study, statistical analysis was performed using analysis of variance (ANOVA). Results: The results revealed a significant difference P<0.05 ANOVA which was shown in blood Ca and Zn parameters before and after treatment, motility, sperm death and sperm abnormality in the rats.Conslusions: In conclusion, supplementation with 100 mg kg-1 WB-1 Timor deer velvet powder will improve the fertility status of male rats.